Effect of Temperature on Ultrasonic Velocities, Attenuations, Reflection and Transmission Coefficients between Motor Oil and Carbon Steel Estimated by Pulse-echo Technique of Ultrasonic Testing Method - Thanh, Pham Van; Nhung, Pham Thi Tuyet; Thuy, Luong Thi Minh; Nhai, Nguyen Hoa (VNU Journal of Science: Mathematics - Physics; Vol 31 No 4, 2015)
In this research, the dependence of the velocities and the absorption coefficients of ultrasonic waves propagated in 1018 low carbon steel on temperature range from 0 o C to 50 o C was investigated. The coefficients of the temperature dependence of the ultrasonic longitudinal wave and ultrasonic shear wave were estimated to be -0.8 m/s. o C and -0.44m/s. o C, respectively. The acoustic impedances of this carbon steel were also investigated and effected much by temperature. Simultaneous, the effect of temperature on the acoustic impedances and ultrasonic attenuations of the motor oil was also determined. As the results, reflection and transmission coefficients at the interface between the carbon steel and motor oil were estimated. It is concluded that the ultrasonic attenuation of the motor oil is one of the main reasons for the behavior of the ultrasonic absorption coefficients propagated in the steel sample. Keywords: Ultrasonic, Nondestructive Testing, Reflection and Transmission coefficients, Longitudinal Wave, Shear Wave, Ultrasonic Velocity, Low carbon steel, Ultrasonic Attenuation, Reflection and Transmission Coefficients, Pulse-echo Technique